Pemanfaatan Media Cyber Konseling Untuk Membentuk Sikap Modernisasi Siswa Di SMA Al-Azhar Medan - Ade Chita Putri Harahap; Ade Bagus Suponco; Addilla Addilla; Ade Putri Wijaya; Alifia Azizah Ilmi; Andini Damayanti; Annisa Febriyani; Dessy Fitasari; Halimah Musfira; Silvi Duwi Nitami (Simpati, 2024)
In this article we include material related to cyber counseling media which is useful for shaping the character or attitude of each student, in this case the development of information and communication technology has had a significant impact on various aspects of human life, including in the field of education . Students in today's digital era tend to be more accustomed to using technology and the internet in everyday life, so it is important to utilize this technology in education. Schools as educational institutions have an important role in shaping students' attitudes and personalities. One aspect that is important to note is the mental health of students. However, there are limitations to conventional counseling services provided by schools, such as limited time and counselors, and the difficulty of student access to counseling locations. Utilization of cyber counseling media can also shape students' modernization attitudes. Students will be accustomed to using technology in everyday life, including in obtaining counseling services. This can help students to improve digital literacy and technology skills which are important in today's digital era